Income Analysis Of Siam Orange Farmers(Citrus Nobilis) In Waitetes Village, Amahai District, Central Maluku Regency - Hendry F Pattiwael; Martha Turukay; Johanna M. Luhukay (International journal of technology and education research, 2023)
The orange commodity is a potential that has an important urgency to be exploited, because it can increase farmers' income and increase export foreign exchange nationally. Amahai sub-district, Waitetes village is one of the citrus producers. Orange farming in Waitetes village is a major advantage for development, because the location of this village is suitable for growing orange fruit and contributes income to farmer households. Oranges are also much-loved by the public as a fresh fruit for consumption. Based on the potential and availability of sufficient land, this village continues to run Siamese orange farming, but farmers in Waitetes village do not have records of farming from the start of production to receipts, and income from their farming. this makes the farming community not aware of the progress of the business they are running. The purpose of this study is to determine the amount of Siamese orange farmers' farming income in the village of Waitetes. The samples taken were all Siamese orange farmers, consisting of 18 people. Analysis of the data used is descriptive. The results showed that the average income of Siamese orange farming in Waitetes Village was Rp. 10,731,696/year. The production factors that have the most dominant influence on increasing the income of orange farmers in Waitetes village are land area and production volume. Analysis of the data used is descriptive. The results showed that the average income of Siamese orange farming in Waitetes Village was Rp. 10,731,696/year. The production factors that most dominantly influence the increase in the income of citrus farmers in Waitetes Village are the area of ​​land and the amount of production. Analysis of the data used is descriptive. The results showed that the average income of Siamese orange farming in Waitetes Village was Rp. 10,731,696/year. The production factors that have the most dominant influence on increasing the income of orange farmers in Waitetes village are land area and production volume.